The Weekly Paper of Caldas: a Publication to Approach Local Science (2019)
The Weekly newspaper was published in the Reino de la Nueva Granada from 1808 to 1810, being the only space to read more scientific than literary or journalistic pieces. They circulated there contents on: "Agriculture, Industry, Trade, Economy, Roads, Navigable Rivers, among others